Modulation of corticospinal excitability in the context of tactile exploration - Oliver, Patricia (University of Ottawa (Canada), 2008)
Evidence indicates that the output of the motor cortex is modulated by task conditions with respect to the degree of dexterity involved. However, few studies have examined how corticospinal output could be modulated when the fingers are used for active exploration of patterns or objects. In the present study, we investigated this issue in young healthy participants with transcranial magnetic stimulation (TMS). Corticospinal excitability of the hand motor representation was examined under two task conditions. One condition (TE: tactile exploration task) consisted of exploring raised letters (6 upper case characters, 6-mm high) with the tip of the index finger for tactile recognition. In the second condition (BP: button pressure task), participants depressed a button with minimal force, again using only the index finger. In both tasks, TMS pulses (110% motor threshold) were delivered over the contralateral motor cortex at a delay of 2500 ms in the course of the 5 second trials. Corticospinal excitability was assessed by monitoring changes in the amplitude of motor evoked potentials (MEPs) in the 1st dorsal interossei (FDI) of each hand. Results (n=18) indicated a differential effect of task conditions on corticospinal excitability, with MEPs being larger during TE when compared to the BP task. These findings suggested that corticospinal excitability could be greatly enhanced when the hand is used for sensory exploration in comparison to simple motor performance. However, electromyographic (EMG) activity patterns differed between the two tasks, which could have contributed to differences observed in motor excitability. Therefore, a secondary experiment was performed with a subset of participants (10/18). In this experiment, motor facilitation elicited with the TE task was contrasted with a finger movement (FM) task. In the latter task, participants reproduced the scanning movements performed when they explored the letter, but no stimuli was presented (smooth surface). The pattern of EMG activity was similar to that elicited in the TE task. Yet, comparisons between the two confirmed the task-specific increase in corticospinal excitability with the TE task. Overall, these results highlight the importance of behavioral demands in modulating corticospinal excitability during hand actions, especially when the finger is used for sensory exploration to acquire information about object and surface properties.
Keywords: Biology, Neuroscience.; Biology, Physiology.